Prevalence and perinatal outcomes in GDM and non-GDM in a rural pregnancy cohort of Bangladesh (Ibrahim Medical College Journal, 2014)
Gestational diabetes mellitus (GDM) or hyperglycemia in pregnancy is associated with adverse perinatal outcomes such as large for gestational age (LGA), excess fetal adiposity and cesarean delivery. This study addressed the prevalence of diabetes in pregnancy and to compare the perinatal outcomes between GDM and non-GDM in a rural pregnancy cohort of Bangladesh. Ten villages were purposively selected in a rural area about 100 km off Dhaka City. A population census was conducted. A randomized sample of married women of age 15-45y was drawn from the census data. These women having either regular menstruation (non-regnant) or cessation of menstruation for ?24weeks (pregnant) were considered eligible. Both the pregnant and non-pregnant women were invited to volunteer the study. Weight, height, waist- and hip-girth and blood pressure were taken. Fasting blood sample was collected for the estimation of plasma glucose (FPG), triglycerides (TG), cholesterol (chol), high-density lipoprotein (HDL). FPG >5.1 mmol/L was taken as cut-off for hyperglycemia in non-pregnant and gestational diabetes mellitus (GDM) for the pregnant women. The biophysical characteristics were compared between pregnant and non-pregnant; and then GDM and non-GDM. Only the pregnant women were taken as a pregnancy cohort. The cohort had followup from 24wks of pregnancy through 28 post-natal days. Results The census yielded 23545 (m / f=11896 / 11649) people of all ages. The married women of age 15-45y were 4526. Of them, 2100 were randomly selected for investigation and 1585 (75.5%) volunteered. The overall prevalence (95% CI) of hyperglycemia (FPG >5.1 mmol/L) was 18.5% (16.7 20.3). The prevalence of GDM was 8.9% (7.0 10.8) and non-GDM was 19.8% (18.8 20.8). The BMI and WHR were significantly higher in the pregnant than non-pregnant women; whereas, there was no significant difference between GDM and non-GDM group. The prevalence rates of abortions, stillbirths, hospital delivery, cesarean delivery, hospital stay ?7days, puerperal sepsis and neonatal death did not differ between GDM and non-GDM subjects significantly. The prevalence of GDM in rural Bangladesh is comparable with any other population with higher prevalence of GDM. The prevalence of hyperglycemia was found significantly higher in the non-pregnant than the pregnant women. The anthropometric measures did not differ significantly between GDM and non-GDM though FPG was found significantly higher in the former. Compared with the non-GDM the GDM subjects had no significantly higher fetomaternal morbidity and mortality possibly due to non-sedentary habit, non-obesity, non-dyslipidemia or may be due to inherent genetic makeup. A well designed study in a larger sample may explain our findings. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20101 Ibrahim Med. Coll. J. 2013; 7(2): 21-27